Pengembangan Komposit Bermatrik Ebonit Dengan Kandungan Sulfur 40 Phr Yang Diperkuat Serat Rami 0 Phr, 30 Phr Dan 50 Phr Untuk Komponen Otomotif - Puji Nugroho, Prasetyo; , Joko Sedyono, ST., M.Eng., Ph.D (2016)
The material used in the industry at this time is dominated by a material which is not friendly to the environment, thus is developed an environmentally friendly material. Composite materials be widely developed to solve the problem, especially composites with natural material for matrix and then combined with natural fibers to achieve an environmentally friendly material. This research use ebonite as a matrix and jute fiber as reinforcement, and then tested to determine the mechanical properties of the composite. The standards used for tensile testing using the standard ASTM D 638 and the highest value of tensile strength in ebonite with a fiber content of jute 50 Phr amounted to 20.246 Mpa, for impact testing using Izod impact with ASTM D 256 the highest impact on the value of ebonite with jute fiber content of 50 Phr of 30,276J/mm2, while for Shore D hardness testing used by the standard ASTM D 2240, the highest value occurred in ebonite with hemp fiber content 82.967 Shore D.